Increasing Efficiency for Document Tracking using Web Technology - Inyaem, Uraiwan; Chomsutta, Anupat; Thanoh, Muhammadsamree; Puangsiri, Pollarat; Ngernplapplar, Sahavit (Journal of Applied Research on Science and Technology (JARST), 2020)
Nowadays, in house and an external organization trading are necessary to have a purchase document-sales to be written between the buyer and the seller. For especially in corporate, the purchase-sales need to check several steps for the details of the purchase document. Which is vulnerable to document loss, missing responsible for tracking documents. From the cooperation government office has found this problem, the researcher proposes the framework of website system for supporting organization. The objective of this research is the employees in the organization easily tracking documents and to prevent document loss issues within an organization. Staffs in the organization of each department can check the address of the document from the document tracking report within the website so increasing efficiency for the organization. The proposed system is developed from the navigation of Joget workflow conjunction with PHP language. The complete proposed system is installed and evaluated form 3 experts and 30 users by using satisfaction assessment questionnaires. The result assessment from expert show that the average value of 4.45 and the standard deviation value of 0.85, and the result assessment form users show that the average value of 4.50 and the standard deviation value of 0.97. The systems can tracking document jobs which is convenience for users and prevent loss of documents within organization.